Student and Teacher Factors as Predictors of Statistics Achievement in Federal School of Statistics Ibadan - Abel Adekanmi Adetona (Institute of Advanced Engineering and Science, 2017)
The study aimed at assessing how students and teachers factor taken together influence students’ achievement in Statistics as well as their relative contribution to the prediction. Two research questions were raised and purposive sampling was adopted to select national diploma year 2 students since they are already in their final level in the school. Intact number of lecturers of Statistics department and year 2 Statistics students were used for the study. Students Questionnaire (SQ), Teaching Staff Scale (TSS), and Statistics Achievement Test (SAT) were used for data collection and analyzed using descriptive and multiple regression. The results showed that the 6 variables taken together had significant contribution to students’ achievement in Statistics and accounted for 80.82% of the variation in students’ achievement in Statistics. It was recommended that stakeholders in provision of Statistics education at the monotechnic institutions level must consider the four variables that contributed significantly to achievement seriously during planning for the Statistics education programmes for optimum achievement of students in Statistics.